Impact of COVID-19 Pandemic among Health Care Providers in Bangladesh: A Systematic Review (Bangladesh Journal of Infectious Diseases, 2020)
Background: The world has been passing the most critical time of the century with the COVID-19 pandemic since late December 2019, and numerous people, including a significant portion of health care providers, got the infection and are still sacrificing their lives.Objective: The study was aimed systematically to assess the severity of the SARS-CoV-2 infection, especially in health care sectors, and to appraise the physical, psychological, and social effects of the COVID-19 epidemic among frontline fighters in Bangladesh.Methodology: The keywords: “COVID-19”, “SARS-CoV-2”, “health care system in Bangladesh”, “health care providers”, etc. were searched to collect the desired articles by utilizing various search engines like google, google scholar, pub med, and science direct journals. Data were extracted and finally, were summarized, discussed, analysed, and reported the study results.Result: Numerous specialist doctors, nurses, and all other healthcare workers are immolating their lives to save human entities amid the current coronavirus pandemic, 2019 (COVID-19). In Bangladesh, till August 9, 2020, 73 doctors, including some senior specialists, died of COVID-19 infection reported by various national newspapers. At the early phase of this epidemic in Bangladesh, around 10% of the total infection was found among health workers, alarmingly reported by the Bangladesh Medical Association (BMA). These frontline fighters are additionally confronting numerous challenges, including psychological sufferings, and furthermore, they are assaulted by the society.Conclusion: Since these fighters are relinquishing their beloved lives to protect us from this brutal virus, we are trying to show our profound gratitude, appreciation, thousands of salutes, and undying tribute to these health care fighters with this publication.Bangladesh Journal of Infectious Diseases, October 2020;7(suppl_2):S8-S15